Implementation Of Presidential Regulation Number 78 of 2021 At The Institution Of Balitbangtan BPTP Bengkulu (The Manager Review, 2025)
This study explores the implementation of Presidential Regulation No. 78 of 2021 on the transformation of BALITBANGTAN BPTP Bengkulu into the Center for the Implementation of Agricultural Instrument Standards (BPSIP). The organizational change involves restructuring, position adjustments, employee transfers, and changes in economic rights. The transition triggered mixed reactions among former BPTP researchers 47% chose to stay under the Ministry of Agriculture in BPSIP, losing their researcher status, while 53% moved to BRIN to maintain it. Using a qualitative approach, the study collected data through in-depth interviews with both groups, field observations, and document analysis. Findings reveal that resistance was driven by long-established organizational culture, job stability, and strong relationships at BPTP, while those accepting the change were motivated by career advancement opportunities at BRIN. The study highlights the need for effective change management, transparent communication, and job security to ensure successful institutional transformation and offers strategic insights for managing organizational change in government agencies.